Pengaruh Penambahan Serat Pinang Terhadap Sifat Fisik dan Mekanik Papan Beton Ringan dengan Fly ash Sebagai Filler - Muhammad Blestynsky Renaldi; Alimin Mahyudin (Universitas Andalas, 2023)
Research has been carried out on the effect of adding betel nut to the physical and mechanical properties of lightweight concrete boards with fly ash as filler. Variation of areca fiber 0.2%; 0.4%; 0.6%; 0.8%;1% by using a random arrangement of fibers. Physical and mechanical properties tested include density, water absorption, porosity, compressive strength, and flexural strength measured by Universal Testing Machine (UTM). Based on the test results, adding areca fiber mass is inversely proportional to density and proportional to porosity and water absorption. The lowest density value in the 1% fiber variation sample is 2 gr/cm3, the lowest porosity value is 19.56% with the composition without fiber and fly ash, and the lowest water absorption value is 9.47% in the composition without fiber and fly ash. Fly ash with betel nut ableto increase the value of the compressive strength and flexural strength of the lightweight concrete board sample. The highest compressive strength value in the addition of fiber is 78.5 kg/cm3 with a fiber composition of 1%, while the highest flexural strength value is 66 kg/cm3 with a fiber composition of 1%. The porosity and water absorption values of the sample had SNI 03-2105-2006 standard. In addition, the compressive strength value obtained from the sample test meets the SNI 03-3449-2002 standard.